The Relationship between “Servant and Lord” as an Approach of Moral Education - Vahid Khasian Sarabi; Gholamreza Raeisian; Mansour Motamedi; Ali Asadi Asl (آموزه‌های قرآنی)
Moral education is one of the valuable topics that various schools have addressed with different approaches. According to the basics and objectives of this issue, the Holy Quran has mentioned approaches for moral education from its perspective. In this research, an attempt has been made to explain the relationship between servant and lord in the Qur'an in a descriptive-analytical way and to present it as a solution of moral education. According to this research, accepting the relationship between servant and lord as the most basic relationship between man and God by man leads to his moral education. The explanation of this matter should be followed in the components obtained from the relationship between the servant and the lord such as ownership, educator, prudent, ruler based on knowledge and wisdom, the absolute power of the lord and praying and obedience of the servant and the manifestations of this obedience and also the result of this relationship which is piety. Therefore, based on the relationship between servant and lord, the Qur'an, in order to accept this relationship by man and as a result of his moral training, has used methods such as proving God's lordship and man’s servitude to a teacher, paying attention to the manifestations of God’s lordship in existence and human life and a teacher inviting to piety based on the relationship between servant and lord.